Drivers of Food Price Inflation in Turkey - World Bank (Washington, DC:, 2022)
Food price inflation has increased persistently in recent years in Turkey with a widening divergence from international food price inflation. The study analyzes the main inefficiencies in the Turkish agricultural sector through the lens of food price formation and discusses the policy actions needed to strengthen the sector’s competitiveness. The results of the analysis show that inefficiencies in agricultural markets, augmented by macroeconomic factors, have put food prices on an upward trajectory. The report findings underscore the need to move away from short-term policy responses to a broader policy strategy aimed at stabilizing prices through increased productivity and improved market linkages. Section one presents an overview of food price dynamics across different agricultural commodities and regions. Section two analyzes various factors that drive food price inflation in Turkey at the national level, grounded in econometric analyses and a literature review. Section three includes an in-depth analysis of regional price formation and transmission for tomatoes, green peppers, and dry onions. Section four presents policy recommendations aimed at tackling the existing inefficiencies in Turkey’s agricultural sector that are contributing to rising food prices.